Effect of Plyometric Training on Vertical Jump Performance in Tennis Athletes - Duran Akbaş; Yunus Tunçer; Pelin Avcı; Işık Bayraktar; Akan Bayrakdar (IUC University Press, 2024)
The aim of this study was to investigate the effect of plyometric training on vertical jump performance in tennis athletes. The research group of the study consisted of 25 volunteer tennis athletes between the ages of 12-17. The average age of the athletes in the experimental group (n=12) was 13.75 ± 2.00 years and the average age of the athletes in the control group (n=13) was 13.23 ± 1.30 years. Plyometric training was applied for 8 weeks. Before and after the training period, height, body weight, active jumping (CMJ), active jump with arms free (CMJFA), horizontal jump (HJ), drop jump (DJ), and squat jump (SJ) tests were performed. When the CMJ, SJ and HJ pre-test-post-test results of the experimental group athletes participating in the study were compared, a statistically significant difference (p < .05) was found. However, no statistically significant difference was found when the CMJFA and DJ pre-test-post-test results of the athletes were compared. Although there was no statistically significant difference, 9,46% positive improvement was found in the CMJFA height and 5,50% positive improvement was found in the DJ height of the experimental group athletes. When the test results of the experimental and control group athletes were compared between the groups, a statistically significant difference (p < .05) was found in the SJ test, while no statistically significant difference was found between the groups in the CMJ, HJ, CMJFA, and DJ tests. While a test × group interaction was observed in the SJ test, this interaction was due to the in-group improvements of the experimental group. In conclusion; Plyometric training is thought to be an effective training to improve vertical jump performance (CMJ, SJ, and DJ) in tennis athletes. Testing the benefits of plyometric training on vertical jump with longer-term interventions (≥10 weeks) will provide researchers with clearer findings.